The blood-brain barrier and brain tumors - van Tellingen, Olaf (Henry Stewart Talks, 2008)
The blood-brain barrier (BBB), Brain tumors/glioblastoma multiforme, Pathobiology, Therapeutic option with chemotherapy, Targeted therapies, Circumvention of the BBB, Drug transporters, Preclinical models
Archived at 2018/10/28